Corpo e cidade: as narrativas urbanas como produção do lugar - Silva, Tatiana de Fátima da (2008)
This research is part of the following question: what is the communicative relationship established between body and environment? The aim is to study how the resident of the city, specifically the city of Sao Paulo, perceives the environment in which he lives and stablishing a communicative relationship with it. Thus, understanding the environmental perception as a condition for the city arouse new information, the research concluded a work camp involving residents of the city to demostrate that, through photographs, their perceptions of the context in which tey live and/or frequent. By the way of example and test of the hipotesis made initially were selected photographs of Cristiano Mascaro, considered by the photographer of Sao Paulo, which portray parts of the city, which served as the comparison with photographs of the residents. By being configured as urban narratives, such records were read an interpreted taking into consideration that are not verbal narratives that allow recognize that way the body is cognitively ownership of the area and to what extent will transform is establishing ties with him communicative. The analyses of the images resulted in the revision of two concepts used by Walter Benjamin for the study of the city: the narrative and the fable. Also important was the study of the Jacques Derrida s concept of desconstruction, and the thought of Vilém Flusser about the photograph. In addition, essential were the work of Milton Santos, Lucrécia Ferrara, Jane Jacobs and Kevin Lynch to undestand concepts such as space, spatial, place, visuality, visibility, image, imagination and its application to Communication Science